2007
DOI: 10.2337/db06-0999
|View full text |Cite
|
Sign up to set email alerts
|

In Mice With Type 2 Diabetes, a Vascular Endothelial Growth Factor (VEGF)-Activating Transcription Factor Modulates VEGF Signaling and Induces Therapeutic Angiogenesis After Hindlimb Ischemia

Abstract: Peripheral arterial disease is a major complication of diabetes. The ability to promote therapeutic angiogenesis may be limited in diabetes. Type 2 diabetes was induced by high-fat feeding C57BL/6 mice (n ‫؍‬ 60). Normal chow-fed mice (n ‫؍‬ 20) had no diabetes. Mice underwent unilateral femoral artery ligation and excision. A plasmid DNA encoded an engineered transcription factor designed to increase vascular endothelial growth factor expression (ZFP-VEGF). On day 10 after the operation, the ischemic limbs re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 37 publications
5
72
1
Order By: Relevance
“…Therefore, the increased levels of surface VEGFR1 on day 10 of ischemia suggests a significant inductive role for VEGFR1 in ischemic signaling outcomes. Previous studies (32,46) have reported no changes in VEGFR1 protein levels in ischemic skeletal muscle compared with nonischemic skeletal muscle on days 3 and 10 after femoral artery ligation, despite an upregulation of VEGF-A protein levels at 3 days postischemia. Although total protein levels may not directly correlate with surface receptor levels, the recruitment of intracellularly localized VEGFR1 may explain the increased VEGFR1 surface levels that we observed.…”
Section: Cd31mentioning
confidence: 98%
“…Therefore, the increased levels of surface VEGFR1 on day 10 of ischemia suggests a significant inductive role for VEGFR1 in ischemic signaling outcomes. Previous studies (32,46) have reported no changes in VEGFR1 protein levels in ischemic skeletal muscle compared with nonischemic skeletal muscle on days 3 and 10 after femoral artery ligation, despite an upregulation of VEGF-A protein levels at 3 days postischemia. Although total protein levels may not directly correlate with surface receptor levels, the recruitment of intracellularly localized VEGFR1 may explain the increased VEGFR1 surface levels that we observed.…”
Section: Cd31mentioning
confidence: 98%
“…In the ischemic and nonischemic gastrocnemius muscles, vascular density was analyzed by immunohistochemistry with a rat anti-mouse CD31 antibody by counting 3 random high-power (magnification ϫ200) fields for a minimum of 200 fibers and was expressed as the number of CD31 ϩ cells per fiber, as described previously. 16 …”
Section: Hindlimb Ischemia Perfusion Recovery Necrosis Score and Hmentioning
confidence: 99%
“…15,16 Perfusion flow in the ischemic and contralateral nonischemic limbs was measured as described previously with the use of a laser Doppler perfusion imaging system (Perimed, Stockholm, Sweden). 15,16 Perfusion was expressed as the ratio of the left (ischemic) to right (nonischemic) hindlimb and was performed immediately after surgery and weekly or biweekly up to 21 or 35 days postoperatively. Perfusion recovery was determined either by the absolute perfusion ratio at follow-up or as the ratio at follow-up minus the ratio immediately after surgery.…”
Section: Hindlimb Ischemia Perfusion Recovery Necrosis Score and Hmentioning
confidence: 99%
“…9,20,21 We therefore tested whether inhibition of miR29a expression is sufficient to improve angiogenesis when VEGF signaling is impaired using VEGFR blocking antibodies in simulated ischemia and high glucose. In HUVECs exposed to simulated ischemia and high glucose, we assessed in vitro tube formation when cells were treated with blocking antibodies against VEGFR1, VEGFR2, and both VEGFR1 and VEGFR2 with and without miR29a inhibitor.…”
Section: Tubes/sp CMmentioning
confidence: 99%